Vocal tract resonances in speech, singing, and playing musical instruments - Wolfe, Joe (HFSP Publishing, 2009)
In both the voice and musical wind instruments, a valve (vocal folds, lips, or reed) lies between an upstream and downstream duct: trachea and vocal tract for the voice; vocal tract and bore for the instrument. Examining the structural similarities and functional differences gives insight into their operation and the duct-valve interactions. In speech and singing, vocal tract resonances usually determine the spectral envelope and usually have a smaller influence on the operating frequency. The resonances are important not only for the phonemic information they produce, but also because of their contribution to voice timbre, loudness, and efficiency. The role of the tract resonances is usually different in brass and some woodwind instruments, where they modify and to some extent compete or collaborate with resonances of the instrument to control the vibration of a reed or the player’s lips, and∕or the spectrum of air flow into the instrument. We give a brief overview of oscillator mechanisms and vocal tract acoustics. We discuss recent and current research on how the acoustical resonances of the vocal tract are involved in singing and the playing of musical wind instruments. Finally, we compare techniques used in determining tract resonances and suggest some future developments.